Pewarisan Kesenian Wayang Golek di Jawa Barat - Soni Sadono; Catur Nugroho; Kharisma Nasionalita (JURNAL RUPA, 2018)
As the improvement of increasingly sophisticated technology and the variety of modern communication media, such as television, radio, magazines, and the internet, the communities experienced a change of communication and entertainment media. So diverse regional arts and culture in Indonesia provides opportunities for various parties to be able to pass on to the younger generation and use it as a medium of communication. One of the local cultural arts passed down from generation to generation is Golek Puppets (Wayang Golek). Wayang Golek indeed been utilized by leaders and government in conveying information, knowledge and teachings to the community. Dissemination of information that is still centred on the urban areas, led to information gap between the people who live in urban areas with the people who live in the countryside. Meanwhile, the condition of people in West Java is still largely residing in rural areas. This is one of the reasons why this medium of Golek Puppet folk art is still used in guarding cultural and values heritage, also as dissemination of information media. This research is related to guarding of cultural heritage and development communication strategy. The theory used in this paper is Heriter La Culture Theory which describes the concept of cultural inheritance. While the method used is the method of phenomenology, where research focused on phenomena or events that are unique and special. In this research, the use of wayang golek folk art as a communication medium is something unique because while technology is more modern, some parties in West Java still maintain the traditional communication media that is, the art of wayang golek show. In the development of wayang golek in West Java, almost all stakeholders involved using the conservation, reinterpretation, and revitalization system.